Lungworm of cattle in Malaysia - Htun, Lat Lat; Abdullah Sani, Rehana; Hassan, Latiffah; Abdul Rahman, Sheikh Omar; S., Jeyabalan; M., Hishammfariz; K., Rohani; E., Azlan; P., Ramli (Malaysian Society of Parasitology and Tropical Medicine, 2010)
Bovine lungworm Dictyocaulus viviparus is highly endemic in temperate regions. However, the occurrence of the lungworm has not been reported in any South East Asian country. The main aim of the present study was to detect the presence of lungworm in cattle in peninsular Malaysia and to examine the morphology of the parasite. A cross-sectional study was carried out in which 602 animals from four large scale government cattle farms and one dairy smallholder farm were sampled. In addition, 283 lungs from 11 abattoirs around the country were examined. Faecal samples were examined using the Baermann technique while post-mortem examination was performed on the lungs. Approximately 5% of faecal samples and 1% of lungs were positive for lungworm. Based on the morphology of adult lungworm, eggs and first stage larvae, Malaysian bovine lungworms were D. viviparus.